Seismic behaviour and strength of reinforced-concrete columns with embedded drain pipe - Nataj, Amir Bahador; Senoy, Serhan; Razaqpur, Ghani (Ice Publishing, 2019)
An experimental investigation was carried out to evaluate the seismic behaviour of 200 x 200 mm(2) reinforced-concrete columns with an embedded drain pipe subjected to monotonic and reversed cyclic loading. Nine full-scale specimens were prepared, including two control specimens without an embedded pipe and seven specimens with a pipe embedded in the column core. Among the latter seven columns, two were highly confined using 8 mm dia. ties with 80 mm spacing, while a 200 mm spacing was used in the other columns. The test results indicated that the pipe adversely affected the column's load-carrying capacity, load-displacement response and ductility. The extent of the adverse effect was found to depend on the level of axial load, the degree of confinement and the distance of the pipe exit from the column base. Due to local stress concentration, some local damage was observed in the vicinity of the pipe exit, but the provision of high confinement in the pipe exit region significantly improved the overall behaviour of the column under reversed cyclic loading.
Keywords: compressive strength; cracks & cracking; failure